Endobronchial mass formation after endobronchial ultrasound–transbronchial needle aspiration mimicking implantation metastasis. Issue 12 (28th October 2015) - Kim, Soo Han; Lee, Yunkyoung; Park, Shinhee; Choi, Chang Min; Jo, Jungmin; Lee, Jae Cheol
Key Clinical Message: Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) has been widely used for diagnosing intrathoracic lymphadenopathy. Here, we present two cases of endobronchial polyp formation after an EBUS‐TBNA for suspicious malignant lymph nodes. An inflammatory polyp should be considered as a possible differential diagnosis for a newly developed mass after an EBUS‐TBNA. Abstract : Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) has been widely used for diagnosing intrathoracic lymphadenopathy. Here, we present two cases of endobronchial polyp formation after an EBUS‐TBNA for suspicious malignant lymph nodes. An inflammatory polyp should be considered as a possible differential diagnosis for a newly developed mass after an EBUS‐TBNA.